perspectives on culture and globalisation - edited by Kimani Njogu (Nairobi Twaweza Communications Ltd, 2017)
In 1996 President Nelson Mandela described Professor Ali A. Mazrui (1933-2014) as ?an outstanding educationist and freedom fighter.? In 2002 the former UN Secretary General Kofi Annan referred to Professor Mazrui as ?Africa?s gift to the world.? Author of more than 35 books and hundreds of articles, Professor Mazrui was an African scholar who treated with uncommon flair a wide-range of themes that included globalization, the triple heritage, peace, and social justice. This volume engages with some of the themes that excited his attention for over six decades. The multidisciplinary essays seek to underline the highlights of Mazrui?s intellectual journey and attest to the fact that he was public intellectual par excellence. Indeed, in 2005, he was named one of the top 100 public intellectuals in the world. This book is a product of a symposium held from 15 to 17 July 2016 in Nairobi, Kenya. The symposium was jointly organized by the Twaweza Communications, Nairobi, Kenya, and the Institute of Global Cultural Studies (State University of New York at Binghamton) which Ali Mazrui created and presided over as the Albert Schweitzer Professor in the Humanities from 1991 to 2014.
Includes bibliographical references and index.
Keywords: Mazrui, Ali AlʼAmin--Criticism and interpretation